Investigating computational thinking among primary school students in Terengganu using visual programming - Osmanullrazi, Abdullah (2022)
Computational Thinking (CT) skills can be defined as the ability to carry out the thought process which utilize the concepts of computer science to solve the problems. It has been regarded as one of the important skills in the 21st century and received considerable attention worldwide. Recent studies have shown that visual programming is one of the efficient tools to develop CT skills. The measurement of CT skills is indicated by CT skills competency. Several countries have introduced CT into the curriculum and Malaysia has taken a bold step to introduce it in 2017 by integrating it into the curriculum. Despite some CT studies have been conducted on the higher education, secondary schools and among the teachers in Malaysia, there is still a lack of studies especially among the primary school students within the context of visual programming. There is still a large gap in term of the investigation of student’s CT skills competency in this aspect. To fill this gap, this study aims to investigate student’s competency on CT skills amongst primary school students in Malaysia using visual programming through the creation of computational artifacts such as animation and games. This study adopted a framework of Brennan and Resnick (2012) in designing the experiment and the assessment of CT skills competency. Quantitative approach was used to measure student’s CT skills of Flow Control, Abstraction, Parallelism, Decomposition, Synchronization, User Interactivity and Logic from their computational artifacts. It also compares the CT skills competency in two different project genres namely animation and games as well as the comparison between the genders. In addition to quantitative methods, a qualitative method of semi-structured interview based on the selected project was conducted after the students completed their projects to identify the strengths and difficulties, they had faced during the project creation. This study had implemented a two-hours per week experiment for eight weeks which had been conducted through the subject of Information Technology and Communication. Participants were 12-year-old students (standard 6) from two schools in Terengganu. The experiment was divided into three phases namely, the introduction of algorithm and Scratch interface, the creation of animation and games and in the final phase, participants were allowed to choose either to develop animation or games as their final project. The findings of this study reveal that although the participants’ CT skills competency in the animation phase is in the Basic level, there is improvement of CT skills competency to the Developing level in the game phase. Study also shows project genre influence students to use different CT skills and there was no significant difference on CT skills competency between the genders. The interview has yielded that motivation, positive feelings, and their understanding of logical statement (Logic) are the student’s strengths while debugging, variables and operators are the most difficult skills to implement. This study contributes to the understanding and provides some insights of how Malaysian Primary Schools students have acquired CT skills competency using visual programming through the creation of computational artifacts. The results of this study could hopefully assist the educators and curriculum developers in planning and designing the learning strategies and materials for CT development especially to the primary school students.